Shining a light on NAD- and NADP-based metabolism in plants. (October 2021) - Smith, Edward N.; Schwarzländer, Markus; Ratcliffe, R. George; Kruger, Nicholas J.
Abstract : The pyridine nucleotides nicotinamide adenine dinucleotide [NAD(H)] and nicotinamide adenine dinucleotide phosphate [NADP(H)] simultaneously act as energy transducers, signalling molecules, and redox couples. Recent research into photosynthetic optimisation, photorespiration, immunity, hypoxia/oxygen signalling, development, and post-harvest metabolism have all identified pyridine nucleotides as key metabolites. Further understanding will require accurate description of NAD(P)(H) metabolism, and genetically encoded fluorescent biosensors have recently become available for this purpose. Although these biosensors have begun to provide novel biological insights, their limitations must be considered and the information they provide appropriately interpreted. We provide a framework for understanding NAD(P)(H) metabolism and explore what fluorescent biosensors can, and cannot, tell us about plant biology, looking ahead to the pressing questions that could be answered with further development of these tools. Highlights: The pyridine nucleotides nicotinamide adenine dinucleotide [NAD(H)] and nicotinamide adenine dinucleotide phosphate [NADP(H)] are central to plant biology. Genetically encoded fluorescent biosensors for NADPH and the NADH:NAD + ratio have been expressed in plants. The application of existing and new biosensors offers opportunities to understand NAD(P)(H) metabolism beyond what is possible with alternative methods.